2020
DOI: 10.1039/c9ew00988d
|View full text |Cite
|
Sign up to set email alerts
|

Mixture effects of drinking water disinfection by-products: implications for risk assessment

Abstract: Disinfection by-products (DBPs) in drinking water have been associated with increased cancer risk but effects of known DBPs cannot explain the mixture effects of disinfected water samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 63 publications
3
50
0
2
Order By: Relevance
“…Common detections of contaminants, which often derive from (e.g., Cu, Pb) or are known to change substantially within (e.g., DBP) distribution systems and premise plumbing, reinforce the previously stated (e.g., Bradley et al, 2020 ; Bradley et al, 2018 ; Bradley et al, 2021 ) importance of assessing drinking-water exposures at the point-of-consumption employing an analytical toolbox that more defensibly represents the breadth and complexity of inorganic and organic contaminant mixtures documented to occur in ambient drinking-water sources (e.g., Bradley et al, 2017 ; Moschet et al, 2014 ). The results are consistent with previous TW exposure studies in PR ( Lin et al, 2020 ; Padilla and Vesper, 2018 ; Yu et al, 2015 ), the US ( Bradley et al, 2018 ; Evans et al, 2019 ; Stoiber et al, 2019 ) and elsewhere ( de Jesus Gaffney et al, 2015 ; Gonzalez et al, 2013 ; Leusch et al, 2018 ; Stalter et al, 2020 ; Tröger et al, 2018 ). In line with Safe Drinking Water Information System (SDWIS) violation reporting (accessible online at U.S. Environmental Protection Agency, 2021d ), however, several measured concentrations of DBP with well-documented public-health concerns, including bromodichloromethane and, more broadly, trihalomethanes (THM), were markedly higher than observed in the previous TW studies by this group (e.g., Bradley et al, 2020 ; Bradley et al, 2018 ; Bradley et al, 2021 ) in the mainland US.…”
Section: Resultssupporting
confidence: 92%
“…Common detections of contaminants, which often derive from (e.g., Cu, Pb) or are known to change substantially within (e.g., DBP) distribution systems and premise plumbing, reinforce the previously stated (e.g., Bradley et al, 2020 ; Bradley et al, 2018 ; Bradley et al, 2021 ) importance of assessing drinking-water exposures at the point-of-consumption employing an analytical toolbox that more defensibly represents the breadth and complexity of inorganic and organic contaminant mixtures documented to occur in ambient drinking-water sources (e.g., Bradley et al, 2017 ; Moschet et al, 2014 ). The results are consistent with previous TW exposure studies in PR ( Lin et al, 2020 ; Padilla and Vesper, 2018 ; Yu et al, 2015 ), the US ( Bradley et al, 2018 ; Evans et al, 2019 ; Stoiber et al, 2019 ) and elsewhere ( de Jesus Gaffney et al, 2015 ; Gonzalez et al, 2013 ; Leusch et al, 2018 ; Stalter et al, 2020 ; Tröger et al, 2018 ). In line with Safe Drinking Water Information System (SDWIS) violation reporting (accessible online at U.S. Environmental Protection Agency, 2021d ), however, several measured concentrations of DBP with well-documented public-health concerns, including bromodichloromethane and, more broadly, trihalomethanes (THM), were markedly higher than observed in the previous TW studies by this group (e.g., Bradley et al, 2020 ; Bradley et al, 2018 ; Bradley et al, 2021 ) in the mainland US.…”
Section: Resultssupporting
confidence: 92%
“…Recent research indicates that ozone oxidizes N -methylamines present in secondary wastewater effluent and generates abundant nitromethane (up to ∼35 μg/L) and that nitromethane is the key intermediate toward halonitromethanes during subsequent chlorination . Halonitromethanes are highly genotoxic and have been observed in disinfected wastewater and recycled wastewater, particularly in systems using ozone as a primary disinfectant or preoxidant, followed by chlorine or chloramines as a final disinfection step. In one study on wastewater reuse with ozone/BAC, ozonation was found to increase the halonitromethane formation potential of wastewater by 8–10-fold, but the identity of the halonitromethane precursors remained unknown . The same study found effective removal of halonitromethane precursors by the BAC step after ozonation, but the treatment efficacy of RO and AOP for halonitromethane precursors was not assessed.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the primary source of disinfection by-products (DBPs) came from the drinking water treatment plant (WTP) [40][41][42]. DBPs were determined in 15 WTPs in Beijing City from various water sources by Stalter et al [40].…”
Section: Disinfection By-products (Dbps)mentioning
confidence: 99%
“…On the other hand, the primary source of disinfection by-products (DBPs) came from the drinking water treatment plant (WTP) [40][41][42]. DBPs were determined in 15 WTPs in Beijing City from various water sources by Stalter et al [40]. They discovered that halogenic acetic acids (HAAs) and trihalomethane (THMs) accounted for 38.1% and 42.6% of all DBPs, respectively, in all treated samples.…”
Section: Disinfection By-products (Dbps)mentioning
confidence: 99%